Galactic Structure in the Outer Disk: The Field in the Line of Sight to the Intermediate-Age open Cluster Tombaugh 1 - Carraro, Giovanni (2017)
We employ optical photometry and high-resolution spectroscopy to study a field toward the open cluster Tombaugh 1, where we identify a complex population mixture that we describe in terms of young and old Galactic thin disks. Of particular interest is the spatial distribution of the young population, which consists of dwarfs with spectral types as early as B6 and is distributed in a blue plume feature in the color-magnitude diagram. For the first time, we confirm spectroscopically that most of these stars are early-type stars and not blue stragglers or halo/thick-disk subdwarfs. Moreover, they are not evenly distributed along the line of sight but crowd at heliocentric distances between 6.6 and 8.2 kpc. We compare these results with present-day understanding of the spiral structure of the Galaxy and suggest that they trace the outer arm. This range of distances challenges current Galactic models adopting a disk cutoff at 14 kpc from the Galactic center. The young dwarfs overlap in space with an older component, which is identified as an old Galactic thin disk. Both young and old populations are confined in space since the disk is warped at the latitude and longitude of Tombaugh 1. The main effects of the warp are that the line of sight intersects the disk and entirely crosses it at the outer arm distance and that there are no traces of the closer Perseus arm, which would then be either unimportant in this sector or located much closer to the formal Galactic plane. Finally, we analyze a group of giant stars, which turn out to be located at very different distances and to possess very different chemical properties, with no obvious relation to the other populations.